Data‐Driven Modification of the LI‐RADS Major Feature System on Gadoxetate Disodium‐Enhanced MRI: Toward Better Sensitivity and Simplicity. Issue 2 (8th July 2021) - Jiang, Hanyu; Song, Bin; Qin, Yun; Wei, Yi; Konanur, Meghana; Wu, Yuanan; Zaki, Islam H.; McInnes, Matthew D.F.; Lafata, Kyle J.; Bashir, Mustafa R.
Abstract : Background: The Liver Imaging Reporting and Data System (LI‐RADS) is widely accepted as a reliable diagnostic scheme for hepatocellular carcinoma (HCC) in at‐risk patients. However, its application is hampered by substantial complexity and suboptimal diagnostic sensitivity. Purpose: To propose data‐driven modifications to the LI‐RADS version 2018 (v2018) major feature system (rLI‐RADS) on gadoxetate disodium (EOB)‐enhanced magnetic resonance imaging (MRI) to improve sensitivity and simplicity while maintaining high positive predictive value (PPV) for detecting HCC. Study Type: Retrospective. Population: Two hundred and twenty‐four consecutive at‐risk patients (training dataset: 169, independent testing dataset: 55) with 742 LR‐3 to LR‐5 liver observations (HCC: N = 498 [67%]) were analyzed from a prospective observational registry collected between July 2015 and September 2018. Field Strength/Sequence: 3.0 T/T2‐weighted fast spin‐echo, diffusion‐weighted spin‐echo based echo‐planar and three‐dimensional (3D) T1‐weighted gradient echo sequences. Assessment: All images were evaluated by three independent abdominal radiologists who were blinded to all clinical, pathological, and follow‐up information. Composite reference standards of either histopathology or imaging follow‐up were used. Statistical Tests: In the training dataset, LI‐RADS v2018 major features were used to develop rLI‐RADS based on their associated PPV for HCC. In an independent testing set, diagnostic performances of LI‐RADS v2018 and rLI‐RADS were computed using a generalized estimating equation model and compared with McNemar's test. A P value <0.05 was considered statistically significant. Results: The median (interquartile range) size of liver observations was 13 mm (7–27 mm). The diagnostic table for rLI‐RADS encompassed 9 cells, as opposed to 16 cells for LI‐RADS v2018. In the testing set, compared to LI‐RADS v2018, rLI‐RADS category 5 demonstrated a significantly superior sensitivity (76% vs. 61%) while maintaining comparably high PPV (92.5% vs. 94.1%, P = 0.126). Data Conclusion: Compared with LI‐RADS v2018, rLI‐RADS demonstrated improved simplicity and significantly superior diagnostic sensitivity for HCC in at‐risk patients. Level of Evidence: 3 Technical Efficacy Stage: 2